2020
DOI: 10.1002/ncp.10600
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Nutrition Prescribing and Order Review Safety Study: The Need for Pharmacist Intervention

Abstract: Introduction: Errors have been reported in the literature to occur at each step of the parenteral nutrition (PN) use process, necessitating standardized processes, clinician competence, and open communication for those involved. This study was performed at Central Admixture Pharmacy Services (CAPS®) in collaboration with the American Society for Parenteral and Enteral Nutrition (ASPEN) with the purpose to study the need for and success of PN pharmacist interventions. Methods: A survey was developed and sent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…There is a general deficit in the processes related to the prescription, validation, composition, preparation, dispensing, and administration of PN. In addition, 23% of the establishments do not have a pharmacist dedicated to the administrative, physicochemical, and clinical validation of PN orders [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a general deficit in the processes related to the prescription, validation, composition, preparation, dispensing, and administration of PN. In addition, 23% of the establishments do not have a pharmacist dedicated to the administrative, physicochemical, and clinical validation of PN orders [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Regarding nutrition areas, studies have shown that skilled nutrition pharmacists could be qualified for order review and verification and prompt rational use between enteral feeding and parenteral nutrition. 18 This study was unique in that we not only put forward a new way of giving consultation recommendations but also promoted the management of anticoagulation, PPIs, and nutrition by giving MIMRs in clinical pharmacists' consultations, and hoped to improve the overall prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%